What does "lignoform" really mean? - Tatti, Dylan; Fatton, Vincent; Sartori, Luna; Gobat, Jean-Michel; Le Bayon, Renée-Claire (My University, 2018)
Among the many studies devoted to deadwood, very few have considered it in a broader ecosystemic context, especially in relation to the underlying humiferous topsoil. In order to fill this gap, we detail here the concept of lignoforms, humus forms strongly linked to deadwood and mostly ignored by humus forms specialists. After presenting the main characteristics of deadwood, the main actors involved in its life cycle and its important and varied roles in many ecosystems, we explain how to describe and study lignoforms. We also propose new diagnostic horizons for these particular humus forms, as well as a classification system, including an identification key (see Appendix A Identification key for lignoforms). Finally, we discuss some important issues pertinent to continuing to improve knowledge of these common but little studied humus forms.
Keywords: Lignoforms; Humus forms; Deadwood; Coarse woody debris; Fine woody debris